2019
DOI: 10.1111/tri.13398
|View full text |Cite
|
Sign up to set email alerts
|

Chronic histological changes in deceased donor kidneys at implantation do not predict graft survival: a single‐centre retrospective analysis

Abstract: Summary The use of preimplantation kidney biopsies (PIKBs) to aid deceased donor kidney utilization decisions is controversial. Outcomes of transplants that had been biopsied after the decision had been made to implant were analysed, in order to determine the association between chronic histological changes at implantation and graft outcomes. A retrospective analysis of transplants between the year range 2006–2015 was performed. Karpinski scores on biopsies were collected, and graft outcomes were analysed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…URs of older donors could theoretically be improved by the use of preimplant kidney biopsies, whose practice and utility vary greatly internationally and nationally . However, in the US biopsies are often cited as the primary reason for kidney discard .…”
Section: Discussionmentioning
confidence: 99%
“…URs of older donors could theoretically be improved by the use of preimplant kidney biopsies, whose practice and utility vary greatly internationally and nationally . However, in the US biopsies are often cited as the primary reason for kidney discard .…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies on this topic are of modest quality and are generally characterized by a high heterogenicity in endpoints studied, technical aspects and histological scores used . While some studies showed a correlation between composite histological scores and graft survival , others did not . In the largest study to date, a registry analysis by Sung et al .…”
Section: Current Methodsmentioning
confidence: 99%
“…The use of preimplantation kidney biopsies to identify and quantify chronic histologic changes was not widespread in the United Kingdom during the study period (11). The evidence base underpinning this approach remains contested (8,(11)(12)(13)(41)(42)(43). A current United Kingdom trial aims to determine if national availability of preimplantation kidney biopsies can increase the utilization of organs from older donors (44).…”
Section: Discussionmentioning
confidence: 99%
“…Deciding which kidneys from older donors should be implanted as two single transplants, as a dual transplant, or which should be discarded is challenging. Although some centers in the United Kingdom and internationally use preimplantation histologic evaluation to help identify which kidneys should be implanted as duals (2,8,9), no clinical or histologic parameters have been widely accepted to aid utilization decisions (10)(11)(12)(13)(14)(15)(16). There is also little clinical guidance regarding recipient selection, and many offering policies for kidneys from older donors are based on donor criteria alone (17,18).…”
Section: Introductionmentioning
confidence: 99%